The Implementation of Communicative Approach in English Language Teaching - Nurdiana Nurdiana (Journal of English Language and Culture, 2017)
One of the objectives of communicative approach is language learners are able to reach communicative competence. The term was first introduced by Dell Hymes in terms of the “appropriateness of sociocultural significance of utterance”. It was later on developed by Canale and Swain (1980, 1983) into four areas of competence: grammatical competence, sociolinguistic competence, discourse competence, and strategic competence. In general, the emphasis of communicative competence is language learners can use the language they learn appropriately. Appropriately in this context refers to all aspects of language, including its culture. Thus, not only should English language learners be knowledgeable of how to speak and write English accurately, but they should also be able to understand its culture so that there will not be understanding when communicating with native speakers of English. Taking this concept into account, the primary objective of this research is to examine the implementation of communicative competence in English classes, particularly the one dealing with cultural competence. The subjects of the research are English teachers who teach General English and English Conversation classes. Their responses to the questions regarding the inclusion and the implementation of cultural competence or components in their classes and in the materials used in teaching-learning sessions are discussed in this study.Keywords: communicative competence and cultural competence